3D geometric analysis of second mesiobuccal canal in permanent maxillary first molar tooth. (4th June 2022) - Khadilkar, Indrani; Nangia, Divya; Chawla, Amrita; Sharma, Sidhartha; Kumar, Vijay; Gupta, Shalini; Logani, Ajay
Abstract: Cone‐beam computed tomography scans exhibiting a second mesiobuccal (MB2) canal were examined. The vertical distance of the MB2 orifice from the pulp floor (depth), inter‐orifice distance (IOD) of MB2 from mesiobuccal (MB) and palatal (P) orifices, the horizontal distance of the MB2 orifice from the line joining MB‐P orifices [mesial deviation (MD)] and root canal configuration (RCC) were evaluated on 330 scans. The Student's t ‐test, ANOVA, Spearman's correlation and linear regression analysis were applied. The MB2 depth was 1.69 ± 0.86 mm. IOD (MB‐MB2, MB2‐P) was 2.18 ± 0.58 mm and 4.63 ± 1.06 mm, respectively. MD was 1.02 ± 0.37 mm. The predominant RCC was Vertucci's type II (75.5%). No correlation of depth with IOD of MB‐MB2 (rho = 0.0367, p  = 0.506) was observed. Significant correlation of depth with IOD of MB2‐P (rho = 0.696, p  < 0.001) and MD (rho = 0.174, p  = 0.001) was established. No association of depth with age and IOD (MB‐MB2) was observed on linear regression analysis. However, a significant positive association was established with IOD (MB2‐P) ( p  < 0.001) and MD ( p  = 0.001).